Cementitious Materials for Stabilizing Clayey Soils In Road Building - Viet Duc, Nguyen (International Journal of Engineering and Technology, 2019)
This paper studies on different cementitious materials for clayey soil stabilization. One-kilometer rural road was taken into consideration. The road was divided into four segments of 250 meters each, which serve for testing four cementitious soil stabilizer materials. The first one was local clayey soil with 5% cement and 5% fine crushed stone; this was considered as reference or conventional method of soil stabilization. The second and third ones were materials with 9% and 5% fly ash respectively apart from 5% cement. Besides, in the third one the chemical admixture was also used with the amount of 5% cement weight. Fly ash was not added into the fourth mix, which uses only 5% cement and admixture. Experiments showed that fly ash can replace cement partially to make the binder materials in stabilization process more economically and environmental-friendly. However, it needs to take into account an expansive issue in case of submergence. Chemical admixture can also be used in combination with cement, since the higher soil strength was observed. Particularly, the expansive issue of clayey soil stabilization would be taken under control while using the admixture. The combined use of cement, fly ash, and chemical admixture yielded the most effective results from technical point of view, however in this case the economic issue should be taken into consideration.Â Â